Islamic Political Economic Strategy in Developing the Economy During the Abbasid Dynasty under the Leadership of Al-Mansur - Shabaha El Rojana; Niadatus Soliha; Anisa Putri (Al-Iffah: Journal of Islamic Sciences Research, 2025)
This study aims to describe the political strategy of Islam during the Abbasid dynasty under the leadership of al-Mansur. This research method was made using a qualitative method using library studies, namely by searching for literature through journals, books and previous research. The results of this study indicate that the strategy of the Caliph al-Mansur began by eliminating various threats to his government, moving the capital of government from Anbar to Baghdad, organizing state administration by forming a vizier and several government employees, implementing economic policies, controlling and stabilizing prices of goods, regulating state revenue sources and tax collection and printing dinar and dirham money.